Seismic Fragility Analysis of Bridge Group Pile Foundations considering Fluid-Pile-Soil Interaction - Chao Zhang; Chengwang Wu; Piguang Wang (Shock and Vibration)
The cross-sea bridges play an important role to promote the development of regional economy. These bridges located in earthquake-prone areas may be subjected to severe earthquakes during their lifetime. Group pile foundations have been widely used in cross-sea bridges due to their structural efficiency, ease of construction, and low cost. This paper investigates the seismic performance of bridge pile foundation based on the seismic fragility analysis. Based on the analysis platform OpenSees, the three-dimensional finite model of the bridge pile foundation is developed, where the pile-water interaction is replaced by the added mass method, nonlinear p-y, t-z, and q-z elements are used to simulate pile-soil interaction, and the displacement of the surface ground motion due to seismic excitations is applied on all spring supports. The seismic fragility curves of the bridge pile foundation are generated by using the earthquake records recommended by FEMA P695 as input motions. The curvature ductility based fragility curves are obtained using seismic responses for different peak ground accelerations. The effects of pile-water interaction, soil conditions, and different types of ground motions on the bridge pier fragilities are studied and discussed. Seismic fragility of the pier-group pile system shows that Sec C (the bottom section of the pier) is the most vulnerable section in the example fluid-structure-soil interaction (FSSI) system for all four damage LSs. The seismic responses of Sec E (a pile section located at the interface of the soil layer and water layer) are much lower than other sections. The parameter analysis shows that pile-water interaction has slight influence (less than 5%) on the fragility curves of the bridge pier. For the bridge group pile foundations considering the fluid-pile-soil interaction, PNF may induce larger seismic response than far-field (FF) and no-pulse near field (NNF). The bridge pile foundation in stiff soil is most vulnerable to seismic damage than soft condition.